Contribution of IL-33 to the Pathogenesis of Colorectal Cancer - Cui, Guanglin; Yuan, Aping; Pang, Zhigang; Zheng, Wei; Li, Zhenfeng; Goll, Rasmus (Frontiers in Oncology, 2018)
The development of colorectal cancer (CRC) is not only determined by transformed cells per se, but also by factors existing in their immune microenvironment. Accumulating scientific evidence has revealed that interleukin (IL)-33, an IL-1 family member, plays an essential role in the regulation of immune response and is relevant in CRC pathogenesis. Data from both human and experimental studies demonstrated that IL-33 inhibits host anti-tumor immunity, remodels tumor stroma and enhances angiogenesis, thereby promoting the development of CRC. These pro-tumor effects of IL-33 are mainly mediated by IL-33 receptor ST2 (also known as IL-1RL1). Based on those findings, it is currently hypothesized that the IL-33/ST2 pathway is a potential biomarker and therapeutic target for colorectal tumorigenesis. Herein, we summarize the recent discoveries in understanding the critical role of the IL-33/ST2 pathway in contributing to the pathogenesis of colorectal tumorigenesis and discuss its potential implications for the future development of effective anti-tumor strategies.